Epigenome-wide association studies identify DNA methylation associated with kidney function. Issue 1 (December 2017) - Chu, Audrey; Tin, Adrienne; Schlosser, Pascal; Ko, Yi-An; Qiu, Chengxiang; Yao, Chen; Joehanes, Roby; Grams, Morgan; Liang, Liming; Gluck, Caroline; Liu, Chunyu; Coresh, Josef; et al.
Abstract Chronic kidney disease (CKD) is defined by reduced estimated glomerular filtration rate (eGFR). Previous genetic studies have implicated regulatory mechanisms contributing to CKD. Here we present epigenome-wide association studies of eGFR and CKD using whole-blood DNA methylation of 2264 ARIC Study and 2595 Framingham Heart Study participants to identify epigenetic signatures of kidney function. Of 19 CpG sites significantly associated (P < 1e-07) with eGFR/CKD and replicated, five also associate with renal fibrosis in biopsies from CKD patients and show concordant DNA methylation changes in kidney cortex. Lead CpGs atPTPN6 /PHB2, ANKRD11, andTNRC18 map to active enhancers in kidney cortex. AtPTPN6 /PHB2 cg19942083, methylation in kidney cortex associates with lower renalPTPN6 expression, higher eGFR, and less renal fibrosis. The regions containing the 243 eGFR-associated (P < 1e-05) CpGs are significantly enriched for transcription factor binding sites of EBF1, EP300, and CEBPB (P < 5e-6). Our findings highlight kidney function associated epigenetic variation. Genome-wide association studies of kidney function show enrichment of associated genetic variants in regulatory regions. Here, the authors perform epigenome-wide association studies of kidney function and disease, identifying 19 CpG sites significantly associated with these.